2014
DOI: 10.1159/000368137
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Pilot Study of Homeopathic Treatment of Attention Deficit Hyperactivity Disorder in Children and Youth

Abstract: Background: An open-label pilot study of individualized homeopathy for attention deficit hyperactivity disorder (ADHD) was conducted to assess the potential for future studies with a focus on the feasibility of the recruitment plan and outcome measure schedules; identification of any group characteristics of participants who respond significantly to the therapy; and establishing the length of time required for an improvement in ADHD symptoms. Patients and Methods: Participants (aged 6-16) were recruited throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…7 However there is currently minimal high quality evidence regarding the clinical effectiveness of complementary and alternative therapies. 9 The peer reviewed evidence base for homeopathy for ADHD to date consists of: six placebo controlled randomised controlled trials (RCTs) testing the efficacy of homeopathic remedies (of which two tested nonindividualized remedies 10,11 and four tested individualized remedies 12e15 ); two observational studies of treatment by homeopaths 16,17 ; and one within subjects trial of treatment by homeopaths measuring ADHD symptoms in ASD. 18 The majority of RCTs of individualized remedies (3/4) showed statistically significant effects, as did the within subjects trial of treatment by homeopaths and the two observational studies; whilst neither RCT of non-individualized remedies showed any effects.…”
Section: Introductionmentioning
confidence: 99%
“…7 However there is currently minimal high quality evidence regarding the clinical effectiveness of complementary and alternative therapies. 9 The peer reviewed evidence base for homeopathy for ADHD to date consists of: six placebo controlled randomised controlled trials (RCTs) testing the efficacy of homeopathic remedies (of which two tested nonindividualized remedies 10,11 and four tested individualized remedies 12e15 ); two observational studies of treatment by homeopaths 16,17 ; and one within subjects trial of treatment by homeopaths measuring ADHD symptoms in ASD. 18 The majority of RCTs of individualized remedies (3/4) showed statistically significant effects, as did the within subjects trial of treatment by homeopaths and the two observational studies; whilst neither RCT of non-individualized remedies showed any effects.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil and France, two from Austria and one each from Canada, Denmark, Belgium and Sierra Leone. rate From these 35 trials, we found 16 publications[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (46%) in MEDLINE and Google Scholar: six were indexed in the trial entry, three indexed and published in MEDLINE and the other seven indexed in…”
mentioning
confidence: 99%
“…Auch in Tierexperimenten [10,11,12,13] und in Pflanzenstudien [14,15,16] treten Effekte in solcher Häufigkeit auf. Entgegen oft gehörten Äußerungen gibt es durchaus auch Modelle, die replizierte Effekte ergeben - etwa das Modell homöopathischer Behandlung von Kindern mit Aufmerksamkeitsdefizit-/Hyperaktivitätssyndrom [17,18], das gerade repliziert wird [19]. Immer wieder gibt es qualitativ hochwertige Pilotstudien, wie die unlängst publizierte von Gassmann et al [20], die zeigen, dass unerwartete Effekte auch unter höheren Potenzen und dokumentiert mit objektiven Methoden zu beobachten sind.…”
unclassified